National Survey of Pharmacy Leadership at Ministry of Health in Saudi Arabia: Practice Management - Alomi, Yousef Ahmed; Abdulmohsen Albaz, Modhi; AlMuhraj, Wejdan Fawzan; AlKharji, Mashael Yasser; Alshuraym, Norah Rushud (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the national survey of pharmacy leadership at the Ministry of Health with emphasis on pharmacy practice. Methods: It is a ninety days cross-sectional national survey of pharmacy leadership practice at MOH hospitals. The survey modified from self-assessment of 360 leadership and with pharmacy leadership literature. It consisted of a demographic section, leadership pathway, and fifty-three leadership questions. It contained selected eighteen leadership skills of 360 leadership self-assessment.The leadership skills included Achievement, Goals, Flexibility, Feedback, Excellence, Empowering Others, Emotional Intelligence, Decision Making, Developing Others, Cultural Awareness, Continual Improvement, Communication Skills, Coworker Development, Leading the Change Needed, Attitude, Analytical, Administrative Skill, and Action. This survey distributed to all leadership at MOH hospital pharmacies in Kingdom of Saudi Arabia. All analysis is done through the survey monkey system. The survey divided into for several parts for analysis, and discussion. Part one: practice management, part two: planning and organizations, part three: communications strategies, part four: problem-solving and decision making, part five: performances management, part six; working environment, and part seven: professional development. The study explored the part number one; National Survey of Pharmacy leadership: practice management. Results: The survey distributed to one hundred hospitals, the response rate, was forty-two hospitals (42%) with seventy-pharmacy leaders. The gender distribution of responders was Male 43 (63.24%) and female 25 (36.76%) while the nationality was Saudi 69 (98.57%) and non-Saudi 1 (1.43%). The average score Aspects before handling the position was 2.45 (49%) with the highest score was received pharmacy administration orientation 2.57 (51.4%), and the lowest score was received pharmacy administration training courses before handling the positions 2.29 (45.8%). The most sources of gaining skills in pharmacy leadership were life experiences 51 (72.86%) and on job training 29 (41.43%). The average score of administration skills that had pharmacy leaders was 3.63 (72.6%) with the highest score of Communication skills 4.15 (83%), and the lowest score of administration skills was Marketing skills 2.62 (52.4%). Most of the pharmacy leaders had is no incremental of the salary of current positions 44 (67.69%), and most of them got 1-5% only if existed. The majority of pharmacy leaders 29 (43.28%) planned to quit the current position. Conclusion: The pharmacy leadership had low satisfaction at a healthcare organization in Saudi Arabia. Targeting of established very comprehensive leadership program with an emphasis on pharmacy leadership is a requirement for Ministry of Health institutions leads to improve the pharmacy services offered to the patients.
Keywords: Pharmacy leadership; Practice management; Ministry of health; Saudi arabia